Transnationalisierung als Widerstand: Indigene Reaktionen gegen fremdbestimmte Ressourcennutzung im Osten Kanadas - Soyez, Dietrich; Barker, Mary L. (ERDKUNDE, 1998)
This paper addresses transnational indigenous resistance against externally controlled resource use and its negative externalities in eastern Canada (i.e. the large scale James Bay hydroelectric development and the Goose Bay based military low-level flight activities by the air forces of four NATO countries in eastern Quebec and the Labrador part of Newfoundland). Drawing on recent conceptual ideas developed in Geography, Political Sciences, and Anthropology it is argued that - partly due to the fragmentation of traditional power geometries - formerly marginalized actors have developed consistent, and sometimes successful, strategies of transnational resistance and embarrassment. These put national and provincial governments as well as corporations under heavy pressure by what has been called ’politics of scale’. This capacity, however, depends on the one side on the actors’ ability to develop appropriate framing, agenda-setting and coalition-building strategies abroad, and on the other side on the weak spots of resource development proponents. A good example for this is the Province of Quebec’s vying for independence and the ensuing desire not to let its reputation in the international community be tarnished by indigenous pressure. The transnational resistance and counter-resistance networks and their flows of ideas, pressure, money, images and so forth can be conceptualized as ’spaces of flows’. These lead to new transnational geographies - called ’scapes’ - which heavily influence the main actors’ behaviour and thus induce, eventually, new patterns of social and spatial change.